Religion and Cult in the Dodecanese during the First Millennium BC Proceedings of the International Archaeological Conference - Stefanakis, Manolis I.; Mavroudis, Georgios; Seroglou, Fani K. (2023)
Religion and Cult in the Dodecanese during the First Millennium BC publishes the proceedings of the conference of the same name, held in Rhodes in October 2018. Religion has always been one of the major components of peoples' lives, an integral part of social, economic and political contexts, contributing to the formation of culture and history. In order to study and understand the religious and cult practices of a particular region, it is necessary to explore their various expressions through material culture and written sources. The oldest known cult remains in the Dodecanese can be dated to the end of the 10th and early 9th centuries BC and throughout the 1st millennium BC. They demonstrate the existence of a vibrant island society with various evolving cult practices. As a major stopover on maritime trade routes, the southeastern Aegean was influenced by contacts from throughout the Greek world and beyond. The contributions to this volume draw on archaeological and literary sources to explore both the development and continuity of cults in the Dodecanese, from the Early Iron Age through to the 1st century BC.